The Effect of Speed Endurance Training on Increasing Aerobic Endurance of Futsal Extracurricular Students - Febriliana, Fanesa Amanda; Kusnanik, Nining Widyah; P. Bird, Stephen (Universitas Negeri Surabaya, 2025)
Purpose: This study aims to analyze the effect of speed-endurance training on increasing aerobic capacity (VO₂max) among students participating in extracurricular futsal activities. Materials and Methods: This study involved 35 male futsal extracurricular students divided into an experimental group (n = 20; age 14.70 ± 0.47 years, height 159.20 ± 7.57 cm, weight 53.25 ± 7.61 kg, BMI 20.02 ± 1.59) and a control group (n = 15; age 14.60 ± 0.51 years, height 160.20 ± 2.43 cm, weight 53.80 ± 5.24 kg, BMI 20.93 ± 1.56). The experimental group underwent four weeks of Speed Endurance Soccer Training (SEST), while the control group participated in regular futsal training. Aerobic endurance (VO₂max) was measured using the beep test during pretest and posttest. Statistical analysis using SPSS 27 revealed normally distributed residuals (Shapiro–Wilk p = 0.053) but unequal variances (Levene's test p < 0.001); therefore, Quade's nonparametric ANCOVA with the pretest as a covariate was applied, followed by pairwise comparisons. Significance was set at p < .05. Result: All variables were normally distributed (Shapiro–Wilk p = 0.053), but the homogeneity assumption was violated (Levene’s test p < .001). Therefore, the data were analyzed using Quade’s nonparametric ANCOVA, which showed a significant group effect after controlling for the pretest scores (F(1,33) = 46.70, p < .001). Pairwise comparison confirmed that the experimental group achieved significantly higher posttest VO₂max scores than the control group (t(33) = −6.83, p < .001). Conclusion: Speed-endurance training effectively improved students' aerobic capacity and proved to be a practical, efficient method that can be readily implemented in school-based futsal training programs.